Clinicopathological Significance of HER2/neu Expression in Gastric Carcinoma - Manta, Ashim; Medhi, Pranita (Annals of Pathology and Laboratory Medicine, 2019)
Background: Gastric cancer remains the most common cause of cancer related death worldwide. HER2/neu protein overexpression in gastric carcinoma was found to be an independent indicator of poor prognosis. The present study was designed to evaluate the frequency of HER2/neu expression in gastric carcinoma, and also the relationship between HER2/neu expression with clinicopathological parameters. Methods: Analysis of HER2/neu expression was done by immunohistochemistry in 41 specimens of Gastric carcinoma over a period of one year and was correlated with clinicopathological parameters. Samples with IHC score 2+ and 3+ were taken as HER2 positive. Result: The study revealed 15 (36.6%) cases of gastric carcinoma being positive for HER2/neu. Of the 41 cases, 5 were classified as score 3+ (12.2%), 10 were classified as score 2+ (24.4%), 11 were classified as score 1+ (26.8%) and 15 were classified as score 0 (36.6%). Peak incidence was found in the age group of 41-50 years. Significant correlation of HER2/neu expression was found with intestinal type (p-value=0.003) and also with moderately differentiated type (p-value=0.018) of gastric adenocarcinoma. However, no significant correlation was found with the other clinicalpathological parameters like age, sex, site, lymph node status and staging. Conclusion: HER-2/neu over-expression was significantly associated with intestinal type and moderately differentiated gastric carcinoma. HER2/neu status can be considered as an important prognostic factor in gastric carcinoma.